Chronological analysis of the gut microbiome for efficacy of atezolizumab‐based immunotherapy in non‐small cell lung cancer: Protocol for a multicenter prospective observational study. Issue 19 (5th September 2022) - Shoji, Fumihiro; Miura, Naoko; Tagawa, Tetsuzo; Tsukamoto, Shuichi; Okamoto, Tatsuro; Yamazaki, Koji; Hamatake, Motoharu; Takeo, Sadanori
Abstract: Background: Cancer immunotherapy with immune checkpoint inhibitors (ICIs) is an innovative treatment for non‐small cell lung cancer (NSCLC). Recently, the specific composition of the gut microbiome before initiation of cancer immunotherapy has been highlighted as a predictive biomarker in patients undergoing cancer immunotherapy, mainly in the US or Europe. However, the fact gut microbiome status is completely different in races or countries has been revealed. In addition, how the microbiome composition and diversity chronologically change during cancer immunotherapy is still unclear. Methods: This multicenter, prospective observational study will analyze the association between the gut microbiome and therapeutic response in NSCLC patients who received atezolizumab‐based immunotherapy. The aim of the present study is to clarify not only how the specific composition of the gut microbiome influences clinical response in NSCLC patients but the chronological changes of gut microbiota during atezolizumab‐based immunotherapy. The gut microbiota will be analyzed using 16S rRNA gene sequencing. The main inclusion criteria are as follows: (1) Pathologically‐ or cytologically‐confirmed stage IV or postoperative recurrent NSCLC. (2) Patients ≥20 years old at the time of informed consent. (3) Planned to treat with atezolizumab‐based immunotherapy combined with platinum‐based chemotherapy (cohort 1) and monotherapy (cohort 2) as a first immunotherapy. (4) Patients to provide fecal samples. A total of 60 patients will be enrolled prospectively. Enrollment will begin in 2020 and the final analyses will be completed by 2024. Discussion: This trial will provide more evidence of how gut microbiota composition and diversity chronologically change during cancer immunotherapy and contribute to the development of biomarkers to predict ICI response as well as biotic therapies which enhance the ICI response. Abstract : This multicenter, prospective observational study will analyze the association between the gut microbiome and therapeutic response in non‐small cell lung cancer (NSCLC) patients who received atezolizumab‐based immunotherapy. The aim of the present study is to clarify not only how the specific composition of the gut microbiome influences clinical response in NSCLC patients but the chronological changes of gut microbiota during atezolizumab‐based immunotherapy. A total of 60 patients will be enrolled prospectively and this trial will provide more evidence of how gut microbiota composition and diversity chronologically change during cancer immunotherapy and contribute to the development of biomarkers to predict immune checkpoint inhibitors (ICI) response as well as antibiotic therapies to enhance the ICI response.